(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
In this paper, we propose a smart parking system detecting and finding the parked location of a consumer’s vehicle. Using ultrasonic and magnetic sensor, the proposed system detects vehicles in indoor and outdoor parking fields, accurately. Wireless sensor motes support a vehicle location service in parking lots using BLE. In traditional method the devices are expensive and do not connect to a users mobile and data visualization. Hence we proposed an automatic free slot status intimating system.In this proposed system the parking free slot information is send to the IOT . Here obstacle sensors are connected to microcontroller which used to find if the slot is free or not. The slots information is transferred via IOT. If the user is in the zone,they got the data and park the car in the free slot. The slot status is displayed in the LCD. There is no automatic system to monitor the parking slot and allot the free slot to the vehicles in the shopping malls and other places. In this system the advanced sensors network are used to find the free slot and display the data in the LCD and also send to IOT.